Analisis Nilai Budaya Dalam Film Wish Dragon Karya Chris Appelhans - Fachrezi, Fahmy (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2023)
This study aims to describe and analyze the Chinese cultural values ​​contained in the animated film Wish Dragon by Chris Appelhans. Wish Dragon (希望龙) is a 2021 animated film that tells about the friendship between dragon and human named Long and Din. This research is used the theory of sociology of literature and the theory of cultural values. The research method used in this study is a qualitative descriptive method. The data in this study are in the form of conversations spoken by each character that contains Chinese cultural values. The data source in this research is the animated film Wish Dragon released in 2021 by Chris Appelhans with the main character Jackie Chan. Data collection techniques used in this study are listening and note-taking techniques. The researcher analyzes Chinese cultural values ​​through Confucianism and Taoism approaches. This Chinese cultural value is found in conversations between the main characters, namely Din, Long and Lina. Researchers found that there were 6 data on Chinese cultural values ​​in the Wish Dragon movie. Among them are divided into 3 cultural values ​​in Confucianism, namely the principle of Xiao (respect), the philosophy of humanism, and the concept of Yi (benevolence). 3 Taoism cultural values ​​which include Yin and Yang in food, doing good (te) and Yin and Yang in chi.